The effectiveness of hybrid learning as instructional media amid the COVID-19 pandemic - Sumandiyar, Adi; Husain, Muh. Najib; Genggong, Marsia Sumule; Nanda, Indra; Fachruddin, Sutiyana (Jurnal Studi Komunikasi, 2021)
The COVID-19 pandemic has struck the world, prompting the enforcement of stay-at-home policies to halt the spread of COVID-19. Indonesia is not exempted from this situation. The COVID-19 pandemic has necessitated social distance due to social distancing, quarantine, and isolation to minimise the spread of the virus. During the COVID-19 pandemic, an online learning system was used. The ideal learning methods in the new normal era are blended learning and hybrid learning methods. Online learning demands the attention of the communicant so that the message conveyed by the communicator can run effectively. If hybrid learning as an instructional medium can be appropriately utilised, the learning objectives can be achieved. However, in previous studies, the blended learning method still needs to be evaluated so that its application can run well and as expected. Because communication transactions that can overcome various frames of reference or clarify difficulties to transfer understanding in a timely manner are considered rich, the media richness theory is applied in this study. This study aims to know how effective hybrid learning is in Southeast Sulawesi during the COVID-19 pandemic. The method used in this research is phenomenology by involving junior high school teachers in Southeast Sulawesi. Based on this study’s data analysis findings, the Effectiveness of the hybrid learning model in Southeast Sulawesi during the COVID-19 outbreak is decided by students’ and parents’ desire to monitor their children.